Genetic Determinants of IL-6 Levels and Risk of ESKD. Issue 2 (14th February 2023) - Wheless, Lee; Pike, Mindy M.; Chen, Hua-Chang; Yu, Zhihong; Tao, Ran; Bick, Alexander; Chung, Cecilia P.; Robinson-Cohen, Cassianne; Hung, Adriana
Abstract : Key Points: Genetically predicted IL-6 levels are associated with risk of ESKD. Therapeutic modulation of IL-6 could potentially reduce the risk of ESKD.